Low Cost Tertiary Education: The Price to Pay for Knowledge-Business Hub-The Mauritius Transitional Education Case Study - GUNPUTH, Rajendra Parsad (Journal of Education and Vocational Research, 2014)
Most United Kingdom (UK) universities are franchising fast with foreign universities affording low cost tertiary education. Most students and graduates in Mauritius have their degree and other awards from local, Indian or British universities. However, in the recent couple of years UK universities are franchising more and more with local institutions (University of Mauritius and University of Technology Mauritius) with large campuses on the small island of the Republic of Mauritius. Of both French (1715-1810) and British colonisation (1810-1968) until its independence in 1968 the young Republic of Mauritius (12 March 1992) is one of the leading countries in Africa where secondary education is free with a relative weaker fee to enter in tertiary institutions like the University of Mauritius. In a contextualised approach the study that shall follow explain the actual situation transition education in Mauritius where local students are less and less reluctant to go to the UK to have a degree. In return UK universities instead are mushrooming around the island attracting local students who cannot afford to pay high cost tertiary education in countries like the USA, France or the UK. Actually, UK universities are recruiting local academics to lecture on their programmes in Mauritius for local students who despite their high profile cannot afford to pay the fees in the USA or UK. UK universities are also sending their staff to lecture in Mauritius and local students have the same award they would receive in the UK. Indeed, the research reflects to what extent students are willing to remain in Mauritius to avoid obstacles and harassment they would probably face in the UK or the USA in terms of visas, accommodation, job facilities just to name a few. But there is still a cost to pay.